Gender Representation in Otolaryngology–Head and Neck Surgery Recognition Awards. (10th November 2020) - Zambare, Wini V.; Sobin, Lindsay; Messner, Anna; Levi, Jessica R.; Tracy, Jeremiah C.; Tracy, Lauren F.
Abstract : Objective: The proportion of women in otolaryngology–head and neck surgery (OHNS) has steadily increased in recent years. This study examines gender representation in recognition awards given by OHNS societies between 2009 and 2019. Study Design: Retrospective analysis of recognition awards given by 10 OHNS societies between 2009 and 2019. Setting: Retrospective review of web‐based, public records. Methods: Data from 19 awards were analyzed for recipient gender ratio, society, subspecialty, award type (research, achievement, or humanitarian), and change over time. Results: Of 184 awards given by societies in otolaryngology–head and neck surgery, 59 (28%) were given to women. Women received 49 (28%) research awards, 9 (31%) humanitarian awards, and 1 (2.8%) achievement award. Women represented 31% of award winners in rhinology/skull base, 30% of award winners in head and neck surgery, 8% in neurotology, and 6% in facial plastic surgery. The American Head and Neck Society Prevention and Early Detection award had the highest representation of women at 43%. Some awards had no female awardees over the past decade. No temporal trends were observed. Conclusion: From 2009 to 2019, women received recognition awards at a higher percentage than overall gender representation in OHNS. Comparison of research, humanitarian, and achievement awards revealed the disparity of women receiving fewer achievement awards relative to men. Gender representation of award recipients varied by subspecialty, which may be partially determined by gender distribution within the fields.